"Specialling" and "Sitters": What does communication between registered nurses and unregulated workers reveal about care?. Issue 5 (October 2021) - Graham, Frederick; Eaton, Emma; Jeffrey, Carol; Secher-Jorgensen, Heidi; Henderson, Amanda
ABSTRACT: Background: Specialling involves unregulated care workers who, while supervised by registered nurses (RNs), constantly sit with patients at risk of harm. Aim: To describe information exchanges between nurses who "special" people with cognitive impairment experiencing behavioural and psychological symptoms and whether psychosocial strategies are explicitly communicated. Methods: Sequential mixed methods study using online survey (quantitative and qualitative) followed by a group discussion. All Assistants in Nursing (AINs) who worked as "specials' in a large Australian metropolitan hospital were approached to undertake an online survey about specialling that included multichoice questions and free-text responses. Analysis involved univariate statistics and content analysis. Subsequent discussion with a convenience sample of AINs explored content revealed in survey responses. Findings: Of 186 possible AINs, 139 (74.7%) undertook the survey and 14(7.5%) participated in the group discussion. Only 27% reported receiving start-of-shift handovers from an RN, and just 9.4% gave an end-of-shift handover to their RN. Some AINs reported receiving hourly over-the-shift communication with their RNs while others reported receiving none. Mostly, AINs received information about physical tasks, not psychosocial care. Discussion: Psychosocial information about patients was communicated considerably less than physical care, suggesting planned non-pharmacological strategies for behavioural and psychological symptoms were either absent or deprioritised. Although exemplary work interactions existed, there were also inadequate interactions regarding care provision highlighting a lack of RN oversight for those nominally under their supervision. Conclusions: This examination of AINs' self-reports, suggests that important psychosocial information is not communicated in specialling, possibly preventing resolution of patient symptoms and perpetuating risks.